Patterns, processes and models - an analytical review of current ambiguous interpretations of the evidence for pre-Pleistocene glaciations - Molén, Mats O. (Geologos, 2023)
Models (paradigms) and former interpretations have often been presupposed when conducting field research. In the 19th century diamictites were for the first time interpreted to have originated from ancient glaciations. These interpretations have to a large part prevailed in the geological community, although there has been much progress in the areas of sedimentology, glaciology and physical geography. The present work is an effort to find criteria which most clearly discriminate between geological features produced by different processes, mainly glaciation and mass flow, the latter predominantly sediment gravity flows. Geological features which have been interpreted to have formed by glaciation throughout pre-Pleistocene Earth history are compared to similar-appearing geological features formed by mass flow and tectonics, so as to uncover variations in the appearance between features resulting from these different processes. The starting point for this comparison is documentation of the appearance of Quaternary products of erosion and deposition, in order to discern the origin of older formations. It is shown that the appearance and origin of pavements, dropstones, valleys, small-scale landforms, surface microtextures and most other geological features may in some cases be equivocal, but in others the details are indicative of the process which generated the feature. Detailed geological field data which have been compiled by geologists from outcrops of pre-Pleistocene strata, more often than is considered in most papers, commonly point to a mass flow origin, mainly a sediment gravity flow origin, rather than a glaciogenic origin. A process of multiple working hypotheses or interpretations is therefore advocated, based mainly on a comparison of the appearance of features formed by different geological processes documented from different research disciplines. Instead of starting with current interpretations or models, this multiple working hypothesis or methodology helps to avoid confirmation bias and jumping to conclusions.